GLOCALIZATION OF LEARNING AND CREATION SOURCES FOR FICTION WRITING TEACHING MATERIALS: EXPLORING CREATIVITY IN A LOCAL CONTEXT - Sri Lestari; Sumadi Sumadi (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
This research aims to explore the concept of glocalization in the context of fiction writing instruction in higher education and its impact on the creation of teaching materials relevant to the local context. The primary focus of this study is to understand how the glocalization approach can enrich students' fiction writing learning experiences and support the creation of teaching materials that align with the needs and unique cultural aspects of the local context. The research methodology employed is a qualitative approach with data collection techniques including interviews, classroom observations, and document analysis. Participants in this study include faculty members and students involved in the instruction and creation of fiction writing teaching materials in several creative writing programs at universities. The findings indicate that the glocalization approach in fiction writing instruction encourages the use of local readings, the application of local language, and exploration of themes relevant to the local culture. Moreover, this approach also enhances student engagement in the learning process and strengthens their cultural identity as writers. In the context of creating fiction writing teaching materials, glocalization provides rich inspiration and material for educators to develop engaging materials that cater to the needs and uniqueness of the local culture. This research contributes to understanding the importance of integrating local elements in fiction writing instruction approaches in higher education and highlights the significant role of glocalization in creating relevant and meaningful teaching materials.